Clinical and electrophysiological correlation of peripheral neuropathy in newly diagnosed type 2 diabetes mellitus - Bhuyan, Ashok K.; Appaiah, Sonali (International Journal of Advances in Medicine, 2018)
Background: The study was undertaken to evaluate the prevalence of peripheral neuropathy in newly diagnosed type2 Diabetes mellitus (DM) by clinical examination and nerve conduction study (NCS), and to correlate them with risk factors. Methods: Eighty newly detected cases of type2DM of age ≥18 years attending Endocrinology Department of Gauhati Medical College and Hospital, Assam, India were evaluated. Grading of symptoms and signs was done using the Neuropathy Symptoms Score (NSS) and Neuropathy Disability Score (NDS) respectively followed by NCS. Neuropathy was diagnosed based on abnormal NSS, NDS or NCS. Results: Prevalence of peripheral neuropathy was 68.75 % based on abnormal NCS/NDS/NCS. The most common symptom was presence of paraesthesia in 70.9%, followed by weakness in lower limbs in 16.36%. The most common sign was impairment of vibration perception in 76.3%, followed by absent ankle reflex in 56.36%. Abnormal NCS finding was seen in 55% of patients with neuropathy. Of all the patients with neuropathy, only 2.5% had subclinical neuropathy that is abnormal NCS finding in absence of sign and symptoms. Peripheral neuropathy had significant association with age at diagnosis, presence of hypertension, fasting plasma glucose(FPG), HbA1c, serum creatinine and estimated glomerular filtration rate(eGFR) (p<0.05). On multiple linear regression analysis, only age at diagnosis and FPG were independently associated with neuropathy (p<0.05). Conclusions: Patients with type 2DM have a high prevalence of peripheral neuropathy at diagnosis and very few of them harbour subclinical neuropathy. This study has shown that clinical examination still remains the main tool for detection of neuropathy.